2020
DOI: 10.3747/co.27.5615
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Provider Preferences for, and Barriers to, Cannabis Use in Cancer Care

Abstract: Background Limited research has been conducted about the perspectives of oncology health care providers (hcps) concerning the use of cannabis in cancer care and their potential role in advising patients. We sought to determine the barriers encountered by hcps with respect to medical cannabis and their preferred practices in this area. Methods An anonymous survey about cannabis was distributed to oncology hcps at the Tom Baker Cancer Centre in Calgary, Alberta. The 45-question survey measured the opinions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Many Colleges prohibit or strongly discourage dispensing, providing, or accepting delivery of cannabis for medical purposes, which likely impacts physicians' willingness to recommend cannabis for their patients. In addition, a recent study reported that oncology healthcare providers felt that they lacked the knowledge to recommend cannabis to their patients because they desired the ability to monitor their patients' cannabis use and to prescribe accurate doses 11 ; as a result, physicians did not feel ready, and did not want to, answer patients' questions about medical cannabis. 20,21 To the best of our knowledge, this is the first study that applied the TPB to understand the impact of national legalization of cannabis on cancer survivors' decision to medicate or not medicate with cannabis using qualitative methodology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many Colleges prohibit or strongly discourage dispensing, providing, or accepting delivery of cannabis for medical purposes, which likely impacts physicians' willingness to recommend cannabis for their patients. In addition, a recent study reported that oncology healthcare providers felt that they lacked the knowledge to recommend cannabis to their patients because they desired the ability to monitor their patients' cannabis use and to prescribe accurate doses 11 ; as a result, physicians did not feel ready, and did not want to, answer patients' questions about medical cannabis. 20,21 To the best of our knowledge, this is the first study that applied the TPB to understand the impact of national legalization of cannabis on cancer survivors' decision to medicate or not medicate with cannabis using qualitative methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The CMA believes that physicians should not be gatekeepers because cannabis has not undergone the established regulatory review processes that are required for all prescription medicines. Oncology health‐care providers reported that they lacked sufficient cannabis knowledge to make recommendations to their patients 11 . The lack of readily accessible information in standard medical textbooks regarding dosing requirements and potential side‐effects of cannabis use may make it challenging for physicians when advising their patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys regarding medical cannabis were conducted worldwide among certified medical doctors, pharmacists, and medical faculty students [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Most of these studies reveal problems with the lack of local clinical standards or knowledge about the legal status of medical cannabis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also show that views vary by medical specialty, gender, age, and religiosity [ 12 , 13 ]. Oncologists and palliative care specialists usually advocate strongly for the use of medical cannabis, family medicine, and neurology specialists are more conservative [ 12 , 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. There are also slight differences in the acceptance of incorporating cannabinoids in clinical practice between doctors and medical students living in different geographical locations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%